Analisis Pemanfaatan SIINas Menggunakan Metode SWOT Dalam Mendukung Strategi Pembangunan Industri Berkelanjutan Pemerintah Provinsi Jawa Timur - Damara Hutananto, Raditya; Yekti Condro Winursito (Jurnal Serambi Engineering, 2026)
The National Industrial Information System (Sistem Informasi Industri Nasional/SIINas) is a national platform developed by the Ministry of Industry of the Republic of Indonesia to collect, manage, and present industrial data in an integrated manner as a basis for formulating industrial development policies. In East Java Province, the utilization of SIINas is one of the key instruments supporting sustainable industrial development strategies; however, its implementation still faces various challenges at both the business and local government levels. This study aims to analyse the utilization of SIINas at the Department of Industry and Trade of East Java Province using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) method in order to identify internal and external factors that influence the optimization of the system. A descriptive qualitative approach was employed, drawing on internship activities at the Division of Industrial Facilities, Supervision, and Control (SP3I), including direct observation, informal interviews with officials and business actors, and document analysis related to SIINas, Online Single Submission (OSS), and the Geographical Industry Information System (GIIS). The results show that SIINas has several strengths, such as regulatory obligation, digital recording of industrial data, and online accessibility, but also weaknesses, including complexity of use, limited system integration, and infrastructural constraints in certain regions.